Banki krajowe w procesie rynkowego finansowania przedsiębiorstw - Pyka, Irena (Polish Banks in the Process of Enterprise Market Investment, 2006)
The development of financial engineering, which is stimulated by globalization and internationalionalization of economic processes, is fostering the change of enterprise financing models on an international scale. The big part of their external funding is covered by modern market-based instruments, securitized by the issue of securities or complex combinations of derivatives. In this process the major role is played by banks that act both on their own as well as on behalf of financial markets investors. Integration of the European Union financial markets influences the patterns of commercial banks' functioning in Poland. The paper pinpoints the scope and characteristics of the Polish banks' participation in the market-based financing of an enterprise activity in Poland. Polish banks are involved in the provision of market services focused on Polish enterprises, nevertheless the scope of their involvement vary. The characteristics of their services are diversified in terms of the offered products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 506-515